Lignocellulosic Analysis of Corncob Biomass by Using Non-Thermal Pulsed Electric Field-NaOH Pretreatment - Angky Wahyu Putranto; Sakinah Hilya Abida; Khodijah Adrebi; Arta Harianti (Dept. of Chemical Engineering, Diponegoro University, 2020)
In recent years, the second-generation bioethanol and advanced bio-based material production from biomass are focused on the pretreatment process by separating cellulose components from other components such as lignin and hemicellulose. Therefore, a physicochemical pretreatment method is needed by applying a non-thermal pulsed electric field (PEF) and alkali methods to increase the cellulose availabilities with a short process and low energy input. The aim of this study was to analyze the lignocellulose content of corncob biomass by using non-thermal pulsed electric fields (PEF) and NaOH pretreatment. The pretreatment factors used were the electric field strength of PEF and the pretreatment time. Analysis of the structure and elements of the lignocellulose based on the characteristics of the gravimetric method and SEM-EDX for untreated and treated samples. The results showed that pretreatment of corncobs biomass by using PEF optimally at an electric field strength of 9 kV/cm and pretreatment time of 60 seconds that was increasing cellulose of 40.59% when compared with the control and also decreasing the hemicellulose and lignin content of 12.9% and 2.02%, respectively. Under these conditions, the energy per pulse and specific input energy of PEF required 0.0205 J and 8.72 kJ/L, respectively. The microstructure analysis by using SEM-EDX showed significantly visual differences and was an increase in the percentage of C and O atoms between untreated and treated corncob biomass. Furthermore, the corncob biomass treated by using non-thermal PEF and alkali can become effective and efficient for the next process into cellulose-derived products.Keywords: corncob biomass; pulsed electric field; NaOH; pretreatment; cellulose